Embracing Sustainable E-Wallet for Financial Inclusion in Tanzania - Mandari, Herman; Koloseni, Daniel (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
Formal financial services. Therefore, its sustainability is essential. The study developed a novel model to investigate its sustainability in Tanzania using a structural equation modelling technique (SEM). Three hundred sixty-one (361) questionnaires were collected and used in the data analysis. Results indicate that perceived usefulness, user satisfaction, and perceived security significantly drive the continued usage of e-wallets. Convenience influences the perceived ease of use and usefulness of the e-wallets, and mobility impacts the perceived ease of use. In contrast, reachability impacts the perceived ease of use and usefulness of the e-wallets. Additionally, the study found that compatibility influences the perceived usefulness of e-wallets, and perceived usefulness, in turn, affects the satisfaction of e-wallet users. Moreover, the study confirmed that perceived security moderates the relationships between satisfaction and continuance usage intention of e-wallets, as well as between perceived usefulness and users' attitudes towards e-wallet usage. The study provides theoretical and practical insights into the sustainability of e-wallets in Tanzania.